1984
DOI: 10.1007/bf02677039
|View full text |Cite
|
Sign up to set email alerts
|

Oxyethylated sulfonamides as nonionic soil wetting agents

Abstract: Various N-alkylbenzenesulfonamides of the type ROSO2NHR' , where R is t-butyl, or hydrogen and R' is decyl, octyl, t-octyl, 2-ethylhexyl, hexyl, and butyl, were treated with ethylene oxide (EO) to yield polydisperse adducts R$SO 2N(R')(EO)xH where x is any integer from 2 to 20. Each series of adducts exhibited a range of properties and water solubility. Wetting ability, surface tension, cloud point, and hydrophilic-lipophilic balance (HLB) were related to structure and EO content to determine the most efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
1
10
1
Order By: Relevance
“…In a polydisperse system, where calculated chain length equals actual chain length, a minimum should exist as vaguely seen here for the series where R is heptyl and R' is 2~thylhexyl indicating the region of maximum surface activity. The scatter in the values is considerably greater than found in a previous study (7). However, some observations can be made.…”
Section: Properties Of Oxyethylated Amidescontrasting
confidence: 52%
See 2 more Smart Citations
“…In a polydisperse system, where calculated chain length equals actual chain length, a minimum should exist as vaguely seen here for the series where R is heptyl and R' is 2~thylhexyl indicating the region of maximum surface activity. The scatter in the values is considerably greater than found in a previous study (7). However, some observations can be made.…”
Section: Properties Of Oxyethylated Amidescontrasting
confidence: 52%
“…Further studies of this presumed N ~ O acyl migration are in progress. As noted earlier (7), the initial reaction between the amide and E.O. generally required the longest time (2-10 hr) with this period being much longer for highly branched amides.…”
Section: Synthesismentioning
confidence: 54%
See 1 more Smart Citation
“…Materials. The phenylsulfonamide derivatives were prepared by a co-worker in our laboratory, and their synthesis and wetting properties were described in a previous publication (6). The derivatives were mixtures of polydisperse compounds where n = average ethoxylation (EO), and all were liquid at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…These adducts were characterizcd by good wetting and low water solubility. Subsequent studies ofoxyethylated branched aromatic sulfonamides showed that polydisperse adducts are at least equally as good wetting agents as were homogeneous adducts (9). Aromatic sulfonamides add E.O.…”
mentioning
confidence: 99%